Current issues of teaching general surgery. - M. V. Trofimov; V. P. Kryshen; V. V. Zadorozhnyi; S. I. Barannik; S. O. Muntyan; B. V. Guzenko; T. M. Panikova; P. V. Lyaschenko; N. M. Nor; K. S. Slesarenko (Medičnì Perspektivi)
Analysis of the results of teaching general surgery in a credit-modular system showed that there are issues that need to be solved at different levels. They concern educational and methodological and logistical support of education, the proper methodology of teaching practical skills, the distribution of modular control of mastering level of practical and theoretical knowledge as well as the increase of academic hours a on the discipline in the total and restructuring clinical practice.